2023
DOI: 10.3389/fchem.2023.1114109
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally benign silver bio-nanomaterials as potent antioxidant, antibacterial, and antidiabetic agents: Green synthesis using Salacia oblonga root extract

Abstract: Introduction: The use of plant extracts in the green synthesis of metallic nanoparticles is one of the simplest, most practical, economical, and ecologically friendly methods for avoiding the use of toxic chemicals.Method: Silver nanoparticles (AgNPs) were synthesized, employing a high-efficiency, non- toxic, cost-effective, green, and simple technique that included the use of Salacia oblonga root extract (SOR) as a capping agent compared to synthetic nanoparticles. The use of S. oblonga can be seen in traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Another study demonstrated significant antioxidant effects of AgNPs synthesized from root extract of Salacia oblonga. The activity was attributed to the adsorption of various phytochemical and functional groups on the surfaces of AgNPs . Our results further validate these studies.…”
Section: Results and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Another study demonstrated significant antioxidant effects of AgNPs synthesized from root extract of Salacia oblonga. The activity was attributed to the adsorption of various phytochemical and functional groups on the surfaces of AgNPs . Our results further validate these studies.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The observed value was within the range reported previously. 8 , 17 , 18 UV–vis spectrophotometry is a valuable technique for the characterization and monitoring the synthesis of AgNPs. In addition to light scattering, AgNPs have unique optical properties that enable them to interact with specific wavelength of light.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the PubMed electronic database, the number of articles devoted to the production and potential uses of cerium nanoparticles in medicine and veterinary science has increased over the past 10 years, from 156 in 2012 to 407 in 2022. Researchers have associated the most significant prospects for the use of nanoparticles with the noted increase in the regenerative activity of tissues during traumatic damage (including infected wounds of various etiologies), the restoration of functioning tissue after severe somatic diseases accompanied by the partial necrosis of organs [ 11 , 12 , 13 , 14 , 15 ], and antioxidant [ 16 , 17 , 18 , 19 , 20 ] and antitumor effects [ 21 , 22 , 23 , 24 ] with controlled, targeted drug delivery [ 25 , 26 ]. It is especially worth noting the close attention that has been paid in the modern medical and biological literature to the still difficult-to-predict antibacterial effects that accompany exposure to metal nanoparticles and metal salts with Gram-positive and Gram-negative bacteria [ 20 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf extract–derived silver nanoparticles from S. mulbarica proved to be a better antibacterial agent against E. coli and B. subtilis and also possess the capability of ct-DNA damage via releasing of reactive oxygen species (Espenti et al 2020 ). In recent times, environmentally benign silver bio-nanomaterials have been synthesized from the root extracts of S. oblonga and served as potent antioxidant, antibacterial, and anti-diabetic agents (Dugganaboyana et al 2023 ). Recently, Sabeena et al ( 2023 ) performed a comparative study on chemical and green approaches for synthesis of nanocomposites from leaf extracts of S. reticulata and subsequently characterized for in vivo and in vitro biological properties.…”
Section: Introductionmentioning
confidence: 99%